2018
DOI: 10.2989/16085906.2017.1405824
|View full text |Cite
|
Sign up to set email alerts
|

Estimating risk factors for HIV infection among women in Mozambique using population-based survey data

Abstract: The use of population-based survey data together with sound statistical methods can enhance better estimation of HIV risk factors and explain variations across subgroups of the population. The distribution and determinants of HIV infection in populations must be taken into consideration. We analysed data from the HIV Prevalence and Behaviour Survey in Mozambique aiming to find risk factors associated with HIV infection among Mozambican women. The paper provides a complex survey logistic regression model to exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 35 publications
3
15
0
Order By: Relevance
“…Despite the numerous factors that have been reported elsewhere in the world to be associated with HIV infection, it is possible that there could be peculiar determinants of HIV infection among Mozambican women. In previous studies conducted to provide a road map for the current state and evolution of the Mozambican HIV epidemic within women of reproductive age, women who were formerly married (widowed, divorced or not living with a partner), living in households with female headship, aged 25-29 years and living in richer households had higher odds of being HIV-positive [20]. In another study, HIV was associated with low educational attainment, age of first sex for money, current age and having had a genital ulcer [21].…”
Section: Digital Features Introductionmentioning
confidence: 99%
“…Despite the numerous factors that have been reported elsewhere in the world to be associated with HIV infection, it is possible that there could be peculiar determinants of HIV infection among Mozambican women. In previous studies conducted to provide a road map for the current state and evolution of the Mozambican HIV epidemic within women of reproductive age, women who were formerly married (widowed, divorced or not living with a partner), living in households with female headship, aged 25-29 years and living in richer households had higher odds of being HIV-positive [20]. In another study, HIV was associated with low educational attainment, age of first sex for money, current age and having had a genital ulcer [21].…”
Section: Digital Features Introductionmentioning
confidence: 99%
“…Our study results align with findings from previous epidemiological research demonstrating the strong role of STI history and injection drug or crack cocaine use in HIV acquisition among persons at risk. 2,19,21,22 In addition, previous studies have found that unprotected anal intercourse is associated with increased risk of HIV; an estimated 40% of HIV cases among 18-to 34-year-old women is due to anal sex. 3 Where our study deviates from previous studies is in regard to risk posed by exchanging drugs or money for sex.…”
Section: Discussionmentioning
confidence: 99%
“…2,4,9,10,17,18 Studies have shown that women have a higher physiological risk of contracting HIV and other sexually transmitted infections (STI) compared to men since the vagina is an ideal environment for bacteria and viruses to thrive. [19][20][21] In addition, having a STI increases the risk of acquiring HIV. 19,21,22 Because women are less likely to experience or recognize symptoms for STIs than men, many infections go untreated longer, thus making women more susceptible to HIV.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations